TRADISI KEHAMILAN, PERSALINAN, DAN NIFAS MASYARAKAT BADUY SERTA DAMPAKNYA PADA KESEHATAN IBU: A SCOPING REVIEW - Nurlaili, Helmi (Poltekkes Kemenkes Maluku, 2023)
The problems of reducing Maternal Mortality Rate (MMR) are geographical variations, lack of infrastructure, and cultural aspects. The Baduy community upholds their traditions by rejecting technology. They live in Kendeng mountain. Baduy region contributed the highest of Banten's MMR in 2022 with 6 cases. The researcher analyzed the traditions of pregnancy, childbirth, and postpartum of Baduy community. This scoping review study was conducted in Juni 2021 in the five databases. The scoping review stages include identifying research questions, searching for relevant research, selecting and choosing literature, extracting data, as well as compiling a synthesis and drawing conclusions. The article search used the keywords